OP0189 High Grade Salivary Gland Involvement, Assessed by Histology or Ultrasonography, Is Associated with a Poor Response to Rituximab in Primary Sjögren's Syndrome Patients. (9th June 2015) - Cornec, D.; Jousse-Joulin, S.; Costa, S.; Marhadour, T.; Marcorelles, P.; Berthelot, J.-M.; Hachulla, E.; Hatron, P.-Y.; Goeb, V.; Vittecoq, O.; Nowak, E.; Pers, J.-O.; et al.
Abstract : Objectives: To determine whether the extent of salivary gland involvement, assessed using unstimulated whole salivary flow (UWSF), histological focus score or salivary gland ultrasonography (SGUS), is associated with the response to rituximab in patients with primary Sjögren's syndrome (pSS). Methods: 35 pSS patients form the randomized TEARS study, which compared rituximab to placebo, had either centralized salivary gland biopsy or SGUS, at inclusion. Among rituximab-treated patients, 50% were considered responders according to the Sjögren's Syndrome Responder Index (SSRI)-30 definition of the response at week 24. Results: SGUS score was positively correlated to the focus score (r=0.61) and inversely correlated to UWSF (r=-0.68). Conversely, the focus score was not correlated with UWSF. No patients with grade 4 SGUS score responded to rituximab, compared to 88% of patients with SGUS score ≤3. The median focus score at inclusion was 0.3 (0.0-1.3) in the responders versus 4.0 (2.7-5.3) in the non-responders (p=0.02). Conversely, baseline UWSF was not associated with the response. Conclusions: pSS patients with the highest histologic or morphologic salivary gland involvement do not respond to rituximab after 6 months, suggesting that a single 1gX2 rituximab course could be an unsufficient treatment for patients with the highest salivary gland B cell activity. Disclosure of Interest: None declared